Antiviral cyclic peptides targeting the main protease of SARS-CoV-2. Issue 13 (10th March 2022) - Johansen-Leete, Jason; Ullrich, Sven; Fry, Sarah E.; Frkic, Rebecca; Bedding, Max J.; Aggarwal, Anupriya; Ashhurst, Anneliese S.; Ekanayake, Kasuni B.; Mahawaththa, Mithun C.; Sasi, Vishnu M.; Luedtke, Stephanie; Ford, Daniel J.; et al.
Abstract : RaPID mRNA display was used for the discovery of antiviral cyclic peptides that potently and selectively inhibit SARS-CoV-2 M pro . The most potent inhibitor exhibited a novel binding mode, interacting with residues across the homodimer interface. Abstract : Antivirals that specifically target SARS-CoV-2 are needed to control the COVID-19 pandemic. The main protease (M pro ) is essential for SARS-CoV-2 replication and is an attractive target for antiviral development. Here we report the use of the Random nonstandard Peptide Integrated Discovery (RaPID) mRNA display on a chemically cross-linked SARS-CoV-2 M pro dimer, which yielded several high-affinity thioether-linked cyclic peptide inhibitors of the protease. Structural analysis of M pro complexed with a selenoether analogue of the highest-affinity peptide revealed key binding interactions, including glutamine and leucine residues in sites S1 and S2, respectively, and a binding epitope straddling both protein chains in the physiological dimer. Several of these M pro peptide inhibitors possessed antiviral activity against SARS-CoV-2 in vitro with EC50 values in the low micromolar range. These cyclic peptides serve as a foundation for the development of much needed antivirals that specifically target SARS-CoV-2.